Pengelolaan Perencanaan Keuangan Keluarga Nelayan di Desa Perlis Kabupaten Langkat - Mesran; Surya Darma Nasution; Suginam (Forum Kerjasama Pendidikan Tinggi, 2022)
Perlis Village used to be a mangrove forest, founded by fishermen from Perlis Country, Malaysia. At first they were looking for fish, then they were stranded on the island of Sumatra. Gradually, due to the occurrence of small-scale migration, many residents of Perlis Malaysia also stopped by this Perlis Village. In accordance with the title of community service, managing the financial planning of fishing families in the village of Perlis Langkat, the objectives of this activity are: Provide training on preparing family finances to increase the knowledge of family heads and housewives in managing family finances so they can set aside income for family savings. Provide training on preparing family finances to increase the knowledge of family heads and housewives in managing family finances so they can set aside income for zakat.